Prevalence and determinants of anaemia in South Asian diaspora women residing in Hong Kong: An exploratory cross-sectional study - Gary Ka-Ki Chung; Bulbul Sharma; Danna Camille Vargas; Woohyung Lee; Kai Sing Sun; Heidi Hung; Hasiba Munir; Soniya Pun; Mariem Sharif; Lee Sha Tong; Tsz Lui Tang; Man Hin Chio; et al. (Journal of Migration and Health)
Background: Anaemia has been a significant public health challenge for the South Asian community, in particular women and migrant populations. Despite abundant research in developed Western settings, evidence in urbanized Asian settings is extremely scarce for comparisons. This study aims to assess the prevalence and social determinants of anaemia in South Asian women residing in Hong Kong, an advanced economy in Asia. Methods: Between June 2022 and December 2023, 675 non-pregnant South Asian adult women were recruited through territory-wide outreach health assessments for anthropometric and biomedical measurements, in addition to a survey on self-reported sociodemographic, lifestyle, and health factors. Multivariable ordinal logistic regression was employed to identify the predictors of anaemia severity. Results: The observed prevalence of mild and moderate/severe anaemia (haemoglobin level <12 g/dL) were 26.8 % and 31.4 %, respectively. Findings supported the independent protective role of better diet quality against anaemia severity (aOR=0.40 [95 % CI = 0.22, 0.73] for high diet quality compared to poor diet quality), and that women of reproductive age (aOR=2.36 [1.03, 5.44] for the 35–44 age group compared to the youngest group), having a larger household size (aOR=1.11 [1.01,1.21] per person increase), and staying for a longer period in Hong Kong (aOR=1.83 [1.07, 3.13] for > 7 years compared to < 3 years) were associated with more severe anaemia. Conclusion: The high prevalence of anaemia in our sampled South Asian women in Hong Kong, especially those of reproductive age, was partly attributable to nutrition, acculturation, and cultural preference on larger family size, beyond potential genetic predisposition.